Hidup Sehat, Car Free Day Dalam Acara Hut Palang Merah Indonesia Ke 77 Tahun Di Kota Medan - Afrilla Yus Nasution; Jazila Adelina Lubis; Nadia Salsabila Pasaribu; Nurhaidah Anggraini Putri (Peneliti.net, 2023)
Health reflects a person's life as can be seen from his condition, namely a prosperous life both physically, mentally and socially which can enable people to live productive lives. Health is a stable condition between the human body and soul. The concept of a healthy life is different for everyone, some interpret a healthy life as a lifestyle by eating healthy, and some even think that a healthy life is if you are diligent in regular exercise. Being healthy requires rules, if you live without rules you will live recklessly / arbitrarily. It's not only physical health that is disturbed, but mental health is even more dangerous, because health is very important to be happy in life. The most important requirement for human joy and happiness in this life is physical and mental health. The definition of healthy living is how one can live happily in this world. In this study we used a qualitative research method, in which we conducted interviews with several people who took part in the PMI anniversary event in Medan. By conducting these interviews we can find out how important it is to maintain a healthy lifestyle for ourselves to maintain a healthy diet and maintain the cleanliness of the environment around us.